Analysis of the Physical Quality of Clean Water in Ward I Belawan I Medan Village - Meutia Nanda; Adinda Aulia Ar-ramdhani; Putri, Dian Yustika; Ramania Sabina; Azzahra Ramadhana Nasution; Meida Sari Siregar (Universitas Muhammadiyah Palu, 2024)
The degree of public health is strongly influenced by healthy environmental conditions including the ownership of clean water. The use of water in daily life in neighborhood I of Belawan I Medan Village is almost average using borehole water. The problem raised in this study is the feasibility of using borehole water as clean water for daily needs in Belawan I Village related to the availability of clean water that is not good. The purpose of this study was to determine the physical quality of water in the Coastal Area of Neighborhood I, Belawan I Village. This research method uses descriptive research with a qualitative approach. Total respondents were 44 people with a population of 80 families. The data collection methods used in this study were observation, interview and documentation. Based on the results of observations, it was found that the community in Belawan 1 Village does not yet have access to clean water facilities due to obstacles, and not all people use PDAM water, some also use boreholes for their daily needs. People in Belawan I urban village do not have access to clean water facilities, not all houses use PDAM water due to constraints, some also use boreholes for daily needs. From the results of the research conducted, local governments and related agencies can immediately take steps to improve access to clean water in Belawan I Kelurahan. And not only access to water, but also community education on clean water.